Main principles of post-conflict restoration of the economic status of Donbas - Yefremenko, V.; Gavrysh, O. (Економічний вісник Донбасу, 2018)
In the article main principles of post-conflict restoration of the economic status of Donbas are defined; some macroeconomic indicators are analyzed (Global Competitiveness Index, Index of doing business, Index of Economic Freedom, Investment attractiveness Index) which demonstrate the position of Ukraine in international ratings in recent years; proposals are made to resolve the problems of restoring post-conflict areas. Визначено основні принципи постконфліктного відновлення економічного стану Донбасу, проаналізовано деякі макроекономічні показники (індекс глобальної конкурентоспроможності, індекс ведення бізнесу, індекс економічної свободи, індекс інвестиційної привабливості), які демонструють позицію України в міжнародних рейтингах за останні роки, надано пропозиції щодо вирішення проблем відновлення постконфліктних територій. Определены основные принципы постконфликтного восстановления экономического состояния Донбасса, проанализированы некоторые макроэкономические показатели (индекс глобальной конкурентоспособности, индекс ведения бизнеса, индекс экономической свободы, индекс инвестиционной привлекательности), которые демонстрируют позицию Украины в международных рейтингах за последние годы, даны предложения по решению проблем восстановления постконфликтных территорий.